Automatic stabilisers and economic crisis: US vs Europe - Mathias Dolls; Clemens Fuest; Andreas Peichl (University of Essex, Institute for Social and Economic Research (ISER), 2010)
This paper analyzes the effectiveness of the tax and transfer systems in the European Union and the US to act as an automatic stabilizer in the current economic crisis. We find that automatic stabilizers absorb 38 per cent of a proportional income shock in the EU, compared to 32 per cent in the US. In the case of an unemployment shock 47 per cent of the shock are absorbed in the EU, compared to 34 per cent in the US. This cushioning of disposable income leads to a demand stabilization of up to 31 per cent in the EU and up to 28 per cent in the US. There is large heterogeneity within the EU. Automatic stabilizers in Eastern and Southern Europe are much lower than in Central and Northern European countries. We also investigate whether countries with weak automatic stabilizers have enacted larger fiscal stimulus programs. We find no evidence supporting this view.
Keywords: E32; E63; H2; H31; 330; automatic stabilization; crisis; liquidity constraints; fiscal stimulus; Finanzmarktkrise; Schock; Steuersystem; Öffentlicher Transfer; Antizyklische Finanzpolitik; Wirkungsanalyse; Vergleich; EU-Staaten; USA